2023
DOI: 10.3390/foods12173209
|View full text |Cite
|
Sign up to set email alerts
|

Alfalfa Silage Diet Improves Meat Quality by Remodeling the Intestinal Microbes of Fattening Pigs

Junying Xu,
Xiao Liu,
Hongmin Geng
et al.

Abstract: Because the demand for pork is increasing, it is crucial to devise efficient and green methods to improve the quality and quantity of meat. This study investigated the improvement in pork quality after the inclusion of alfalfa meal or alfalfa silage in pig diet. Our results indicated that alfalfa silage improved meat quality more effectively in terms of water-holding capacity, drip loss, and marbling score. Besides, an alfalfa silage diet can affect the level of fatty acids and amino acids in pork. Further, al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 64 publications
(68 reference statements)
0
2
0
Order By: Relevance
“…The gut microbiota plays an important role in the digestion and absorption of nutrients, as well as in intestinal health. Alfalfa silage feeding was found to modulate the gut microbiota, along with improving meat quality [4]. High-energy feeding affected the meat quality of Tibetan pigs, and this was closely associated with alteration in the gut microbiota [41].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The gut microbiota plays an important role in the digestion and absorption of nutrients, as well as in intestinal health. Alfalfa silage feeding was found to modulate the gut microbiota, along with improving meat quality [4]. High-energy feeding affected the meat quality of Tibetan pigs, and this was closely associated with alteration in the gut microbiota [41].…”
Section: Discussionmentioning
confidence: 98%
“…Among them, dietary intervention is known as one of the most common methods [3]. An alfalfa silage diet improved the fatty acid and amino acid levels in pork [4]. Dietary whole or crushed linseed increased the n-3 PUFA content and showed no deleterious effects on the organoleptic characteristics of pork [5].…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have shown that adding apple pomace-mixed silage to the basal diet could improve the feed conversion efficiency of finishing pigs [24]. Many studies have reported on the improvement in monogastric animal meat quality due to silage feed [25].…”
Section: Silage Feedmentioning
confidence: 99%
“…However, it is worth noting that the quality of silage feed can vary depending on the growth stage at which the forage was harvested for silage production. The choice of growth stage or harvest period significantly impacts the nutritional value and fermentation quality of silage feed [25].…”
Section: Silage Feedmentioning
confidence: 99%
See 1 more Smart Citation